Peran Media Dalam Penanggulangan Stunting di Pemereintah Kabupaten Mojokerto - Mochammad Nur Ramadhani (PAWITRA KOMUNIKA : Jurnal Komunikasi dan Sosial Humaniora, 2025)
Stunting, a condition inhibiting both physical and cognitive growth in children, has garnered global attention within the realm of child health. This study underscores the imperative of promptly addressing stunting, exploring potential remedies, and delineating its enduring consequences. Notably, the pivotal roles of media and the Mojokerto Regency Government are emphasized. The research methodology encompasses literature analysis and statistical data encompassing cohort studies, health surveys, and official reports. The study confirms that stunting can yield far-reaching ramifications, potentially encompassing compromised cognitive development, diminished adult productivity, and susceptibility to chronic illnesses. The media holds a pivotal role in combatting stunting. By imparting nutritional insights, enhancing awareness, and galvanizing public support, the media serves as a catalyst. Precise reporting fosters engagement and the dissemination of pertinent information. Within the realm of stunting, the Mojokerto Regency Government emerges as a central actor. Initiatives span from prenatal nutritional programs to bolstering collaboration, conducting health education, and systematically monitoring infant growth. The fight against stunting assumes paramount importance within the context of sustainable development objectives. Through an encompassing approach integrating media, governmental, and stakeholder roles, stunting rates are projected to dwindle, empowering forthcoming generations for sustainable growth.